C/EBPβ Promotes STAT3 Expression and Affects Cell Apoptosis and Proliferation in Porcine Ovarian Granulosa Cells - Yuan, Xiaolong (Genes (Basel), 2018)
Previous studies suggest that signal transducer and activator of transcription 3 (STAT3) and CCAAT/enhancer binding protein beta (C/EBPβ) play an essential role in ovarian granulosa cells (GCs) for mammalian follicular development. Several C/EBPβ putative binding sites were previously predicted on the STAT3 promoter in mammals. However, the molecular regulation of C/EBPβ on STAT3 and their effects on cell proliferation and apoptosis remain virtually unexplored in GCs. Using porcine GCs as a model, the 5′-deletion, luciferase report assay, mutation, chromatin immunoprecipitation, Annexin-V/PI staining and EdU assays were applied to investigate the molecular mechanism for C/EBPβ regulating the expression of STAT3 and their effects on the cell proliferation and apoptosis ability. We found that over and interfering with the expression of C/EBPβ significantly increased and decreased the messenger RNA (mRNA) and protein levels of STAT3, respectively. The dual luciferase reporter assay showed that C/EBPβ directly bound at −1397/−1387 of STAT3 to positively regulate the mRNA and protein expressions of STAT3. Both C/EBPβ and STAT3 were observed to inhibit cell apoptosis and promote cell proliferation. Furthermore, C/EBPβ might enhance the antiapoptotic and pro-proliferative effects of STAT3. These results would be of great insight in further exploring the molecular mechanism of C/EBPβ and STAT3 on the function of GCs and the development of ovarian follicles in mammals.